A prospective randomised trial comparing insertion success rate and incidence of catheterisation‐related complications for subclavian venous catheterisation using a thin‐walled introducer needle or a catheter‐over‐needle technique. (11th July 2016) - Kim, E.; Kim, B. G.; Lim, Y. J.; Jeon, Y. T.; Hwang, J. W.; Kim, H. C.; Choi, Y. H.; Park, H. P.
Summary: In clinical practice, both a thin‐walled introducer needle and catheter‐over‐needle technique can be used to allow insertion of a guidewire during central venous catheterisation using the Seldinger technique. We compared the incidence of catheterisation‐related complications (arterial puncture, haemothorax, pneumothorax, haematoma and catheter tip malposition) and insertion success rate for these two techniques in patients requiring right‐sided subclavian central venous catheterisation. A total of 414 patients requiring infraclavicular subclavian venous catheterisation were randomly allocated to either a thin‐walled introducer needle (needle group, n = 208) or catheter‐over‐needle technique (catheter group, n = 206). The catheterisation‐related complication rate was lower in the needle group compared with the catheter group (5.8% vs. 15.5%; p = 0.001). Overall insertion success rates were similar (97.1% and 92.7% in the needle and catheter groups respectively; p = 0.046), although the first‐pass success rate was higher in the needle group (62.0% vs. 35.4%; p < 0.001). We recommend the use of a thin‐walled introducer needle technique for right‐sided infraclavicular subclavian venous catheterisation.